2017
DOI: 10.1111/apt.14320
|View full text |Cite
|
Sign up to set email alerts
|

Letter: addition of methotrexate neither restores clinical response nor improves the pharmacokinetic profile of vedolizumab‐treated patients

Abstract: Linked Content This article is linked to Strik et al paper. To view this article visit https://doi.org/10.1111/apt.13994.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 5 publications
2
8
0
1
Order By: Relevance
“…Combination therapy at initiation did not lead to higher early vedolizumab through levels, nor was it predictive of mucosal healing within the first year of treatment. These results are in line with our previous finding that addition of methotrexate neither restored clinical response nor improved the pharmacokinetic profile of vedolizumab‐treated patients . Potential explanation is the low immunogenicity of vedolizumab.…”
Section: Discussionsupporting
confidence: 91%
“…Combination therapy at initiation did not lead to higher early vedolizumab through levels, nor was it predictive of mucosal healing within the first year of treatment. These results are in line with our previous finding that addition of methotrexate neither restored clinical response nor improved the pharmacokinetic profile of vedolizumab‐treated patients . Potential explanation is the low immunogenicity of vedolizumab.…”
Section: Discussionsupporting
confidence: 91%
“…Synergy on efficacy or prevention of immunogenicity may both concur to these positive outcomes. The impact of combotherapy on patients with VDZ has been evaluated in real-world experience cohort studies, but with opposite conclusions [15,21,37,38]. Our study suggested that the use of concomitant IMM did not alter the pharmacokinetics of VDZ either at induction or during maintenance, confirming the results of other studies [15,21].…”
Section: Discussionsupporting
confidence: 73%
“…This has been confirmed in all available real-world data so far, even when using a drug-resistant assay [23, 24]. It might explain why adding an immunomodulator to vedolizumab therapy seems neither to enhance drug levels nor to restore therapeutic response [14, 25].…”
Section: Immunogenicitymentioning
confidence: 82%